English as a Lingua Franca: Lessons for language and mobility - Park, Joseph Sung-Yul; Wee, Lionel (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Greater mobility of people in the globalising world foregrounds the inherent problems of an ideology of language as a bounded entity and the unequal relations of power that shape experiences of mobility. In this paper, we consider how these problems can be interrelated in research on language and mobility through a critical evaluation of current research on English as a lingua franca (ELF), particularly what we refer to as the ‘ELF research project’, exemplified by the work of Jenkins and Seidlhofer. TheELF project aims at a non-hegemonic alternative to English language teaching by identifying a core set of linguistic variables that can facilitate communication between speakers of different linguistic backgrounds. We provide a critical examination of the project by problematising its narrow conceptualisation of communication as information transfer and its inability to address the prejudices that speakers may still encounter because they speak the language ‘differently’. In our discussion, we argue that investigation of language in the context of mobility requires serious rethinking on the level of both theory and political stancetaking: a theory of language that does not take account of the fluid, dynamic, and practice-based nature of language will have considerable difficulty in proposing a cogent critique of social inequalities that permeate the lives of people on the move.